DESIGNING THE FUTURE: DIGITAL SKILLS AND INTELLIGENCE IN HOLISTIC EDUCATION - Erwin Erwin; Sa'i Sa'i; Yosefina Itu (International Journal of Teaching and Learning, 2025)
In today's digital era, digital skills and intelligence have become an important element in education. This study aims to analyse the importance of digital skills integration in the concept of holistic education with the aim of preparing students for future challenges. The research method conducted in this study uses the literature research method. The results found that the integration of digital skills into holistic education enriches the learning process by adding critical and interactive dimensions. Students not only acquire technical knowledge, but also digital intelligence that includes an understanding of cybersecurity, ethics in the use of technology, and critical thinking in searching for information. These results confirm that digital skills help students adapt to the ever-changing professional environment and enhance their active participation in a knowledge-based society.